A comparative study of various diagnostic modalities for female genital tuberculosis in infertility in a tertiary hospital - Eeram; Tiwari, Yati; Gupta, Tripti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Infertility is a complex and emotionally challenging issue that affects millions of people worldwide. Infertility has a detrimental effect on women's social standing and psychological health. The aim of this study is to compare the effectiveness of several diagnostic techniques for female genital tuberculosis (TB) in infertility. Objectives to study various diagnostic techniques in patients with infertility attending Obstetrics and Gynaecology outpatient department (OPD) of Rohilkhand Medical College and Hospital (RMCH), Bareilly. Methods: This was a one-year hospital based cross-sectional comparative study carried out in Department of Obstetrics and Gynaecology, RMCH, Bareilly, from 01 November 2019 to 31 October 2020 in women with age group 18-45 years presented with indications of primary and secondary infertility and the estimated sample size was 50. Results: Highest percentage of cases (48%) have been reported for 21-30 age group, least below 20 age group (2%). The detection rates for acid-fast bacilli (AFB) smear, Lowenstein-Jensen (L-J) culture, Mycobacteria growth indicator tube (MGIT) culture and histopathological examination (HPE), were 4%, 4%, 16% and 12%, respectively. Accuracy of MGIT-960 culture correlating with HPE was found to be 92%. The overall comparative analysis between different methods of diagnosis showed that sensitivity was highest for MGIT-960 (62.5%), however, specificity was found to be 100% for both AFB and LJ culture, while 97.6% for MGIT-960 culture. Conclusions: Our results indicate that MGIT-960 is an efficacious detection strategy for GTB, in cases of female infertility.